Residual strength of corroded ring-stiffened cylinder structures under external hydrostatic pressure - Sang-Hyun Park; Su-Min Lee; Youngjae Yu; Sang-Rai Cho (International Journal of Naval Architecture and Ocean Engineering)
Corrosion damage to submarine pressure hulls is a crucial consideration during the structural design phase because it diminishes the structural strength of a submarine, reducing its operational depth and posing a severe risk to the life of the crew. This necessitates using a validated analytical method to estimate the residual strength and assess the safety of corrosion-affected pressure hulls. This paper presents an experimental and numerical investigation of the residual strength of corroded ring-stiffened cylinders, which are typical components of submarine pressure hulls, the main legs of semi-submersibles, and Floating Offshore Wind Turbine (FOWT) foundations. Four steel ring-stiffened cylinder models were fabricated: two remained intact, whereas the other two were artificially corroded by machining. Hydrostatic collapse tests were conducted in a pressure chamber. To evaluate the effect of initial shape imperfections caused by welding fabrication on the strength of the structure, the initial shape imperfections were measured using a three-dimensional coordinate measuring machine. The experimental results illustrate a significant reduction in the residual strengths of the two damaged models compared with those of the intact models. The collapse processes simulated using the Abaqus software package are presented, demonstrating a close agreement between the experimental results and numerical predictions.